2021
DOI: 10.3389/fspor.2021.757253
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes and Relationships in Training Loads, Neuromuscular Performance, and Recovery and Stress State in Competitive Female Soccer Players

Abstract: Background: The purpose of this study was to examine seasonal changes in training load (TL), neuromuscular performance, subjective recovery, and stress state, and to investigate the relationships between acute and chronic TL and neuromuscular performance in competitive female soccer players.Methods: Nine competitive female soccer players (20.0 ± 1.7 years; 60.3 ± 6.3 kg; 164.0 ± 5.8 cm) completed the Short Recovery and Stress Scale and the countermovement jump (CMJ) with polyvinyl chloride pipe (CMJ0) and 20 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…3 To minimize the negative aspects of training, clinicians have begun relying on wearable devices to capture internal and external training loads. [4][5][6][7] These measures aid in predicting injury 1,[6][7][8] and performance capabilities, 5 in addition to having impacts on athlete wellness measures. [9][10][11] Tracking training loads is now extremely clinically feasible, 4,12,13 however, there are numerous methods of tracking training loads, such as global positioning systems, 10,12,14 heart rate monitors, 6,15,16 and accelerometers.…”
Section: Introductionmentioning
confidence: 99%
“…3 To minimize the negative aspects of training, clinicians have begun relying on wearable devices to capture internal and external training loads. [4][5][6][7] These measures aid in predicting injury 1,[6][7][8] and performance capabilities, 5 in addition to having impacts on athlete wellness measures. [9][10][11] Tracking training loads is now extremely clinically feasible, 4,12,13 however, there are numerous methods of tracking training loads, such as global positioning systems, 10,12,14 heart rate monitors, 6,15,16 and accelerometers.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, current evidence (1,8,30,35,42) has indicated that soccer players tend to accumulate different ITL and ETL depending on the competition phase and player position. Ishida et al (19) reported that a 7-day average of total distance covered statistically increased from the preseason to the midcompetitive season ( p = 0.02), whereas the countermovement jump height was statistically higher at midseason compared with baseline ( p = 0.03) in NCAA Division I women's soccer players. Abbott et al (1) also reported that central midfielders covered the greatest distance compared with other positions ( p < 0.01) in U23 Premier League academy male players.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Delaney et al (10) indicated that physical preparedness measured by the ratio between ITL and ETL increased over the 7 weeks in professional rugby players. Based on current evidence (1,4,10,14,19,24,26,35), contextual variables such as competition phase and player position would play an important role in accurately assessing the relationship between ITL and ETL. In particular, it is expected that players could demonstrate a higher ITL in response to a given ETL during the early competitive phase regardless of player position because of low physical preparedness (10,19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations